Crystalline Hydrogen‐Bonded Organic Chains Achieving Ultralong Phosphorescence via Triplet–Triplet Energy Transfer. Issue 12 (4th May 2020) - Liu, Bai‐Tong; Liu, En‐Ping; Sa, Rong‐Jian; Liu, Tian‐Fu
Abstract: Ultralong organic phosphorescent (UOP) materials without any metal species have broad application prospects in optical technologies and biological imaging due to the low cost and biocompatibility. However, it is still a challenge to prepare new UOP materials with long luminous life and high photoluminescence quantum yield (PLQY). Herein, two organic molecules, 1, 4‐phenylenebisboronic acid (PBA) with high PLQY and isophthalic acid (IPA) with long lifetime, are orderly combined into two crystalline hydrogen‐bonded organic chains, named as PBA‐IPA1 and PBA‐IPA2, through supramolecular self‐assembly. Compared with PBA‐IPA1, PBA‐IPA2 shows much improved phosphorescent lifetime (1.59 s) and PLQY (15.72%) due to the triplet–triplet energy transfer between two components, which is further confirmed by computational studies. The obtained material can be potentially used in such areas as information encryption and fingerprint identification, providing a new strategy for design of UOP materials for practical applications. Abstract : Two crystalline hydrogen‐bonded materials (PBA‐IPA1 and PBA‐IPA2) are synthesized through supramolecular self‐assembly. Compared with PBA‐IPA1, PBA‐IPA2 shows improved afterglow property with higher photoluminescence quantum yield and long lifetime due to the triplet–triplet energy transfer, which is further confirmed by computational studies. This study provides a new strategy for design of ultralong organic phosphorescent materials for practical applications.